2020
DOI: 10.1002/anie.201915212
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructive Reorganization: De Novo Synthesis of Hydroxylated Benzofuran

Abstract: An unprecedented deconstructive reorganization strategy for the de novo synthesis of hydroxylated benzofurans from kojic acid‐ or maltol‐derived alkynes is reported. In this reaction, both the benzene and furan rings were simultaneously constructed, whereas the pyrone moiety of the kojic acid or maltol was deconstructed and then reorganized into the benzene ring as a six‐carbon component. Through this strategy, at least one free hydroxyl group was introduced into the benzene ring in a substitution‐pattern tuna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 105 publications
0
21
0
1
Order By: Relevance
“…As shown in Table 1, we initially treated 1a with n-BuLi at −40°C for 1 h and then quenched with MeOH; a new major product 2a and a minor product 3a were isolated (entry 1). The standard analysis, including 1 H nuclear magnetic resonance (NMR), 13 C NMR and mass spectroscopy, was not able to identify these compounds. Gratifyingly, the X-ray analysis showed that 2a was a thiete sulfone and 3a was a propargyl sulfonamide (…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1, we initially treated 1a with n-BuLi at −40°C for 1 h and then quenched with MeOH; a new major product 2a and a minor product 3a were isolated (entry 1). The standard analysis, including 1 H nuclear magnetic resonance (NMR), 13 C NMR and mass spectroscopy, was not able to identify these compounds. Gratifyingly, the X-ray analysis showed that 2a was a thiete sulfone and 3a was a propargyl sulfonamide (…”
Section: Resultsmentioning
confidence: 99%
“…6f, (β-13 C)-1a was prepared and subjected to the standard reactions. 13 C-2a and 13 C-3a could be formed smoothly under standard conditions. The position of 13 C-labelled carbon atom in the products was identified, which indicated that phenyl migration did not occur in these skeleton reorganization processes.…”
Section: E N D O -mentioning
confidence: 92%
See 1 more Smart Citation
“…We initially set the reaction using n-BuLi at -40 o C for 1 hour and then treated with MeOH, and a new major product 2a and a minor product 3a were observed (entry 1). The standard analysis, including 1 HNMR, 13 CNMR and mass spectroscopy, was not able to identify these compounds. Gratifyingly, the X-ray analysis showed that 2a was a thiete sulfone and 3a was a propargyl sulfonamide, indicating an unusual skeletal reorganization occurring.…”
Section: Reaction Optimizationmentioning
confidence: 93%
“…Very recently, Zhu and coworkers reported a novel skeletal reorganization of kojic acid or maltol-derived alkynes under Indium-catalysis, which provided an expeditious access to valuable hydroxylated benzofurans ( Fig. 1d) 13 . Despite these advances, the investigation of skeletal reorganizations toward synthetically challenging and biologically interesting molecules remains continuous interesting and important.…”
mentioning
confidence: 99%